2019
DOI: 10.1096/fba.2019-00053
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the R‐region interactions depend on phosphorylation and contribute to PKA and PKC regulation of the cystic fibrosis transmembrane conductance regulator chloride channel

Abstract: The CFTR chloride channel is regulated by phosphorylation at PKA and PKC consensus sites within its regulatory region (R-region) through a mechanism, which is still not completely understood. We used a split-CFTR construct expressing the N-term-TMD1-NBD1 (Front Half; FH), TMD2-NBD2-C-Term (Back Half; BH), and the R-region as separate polypeptides (Split-R) in BHK cells, to investigate in situ how different phosphorylation conditions affect the R-region interactions with other parts of the protein. In proximity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…Here, we demonstrate how the requirement for S903 phosphorylation is also linked to transport activation. Nonetheless, CFTR studies have shown that combined PKA and PKC stimulation can drastically increase R-domain complex formation and activation (23, 46, 47). The phosphorylated S903 site phosphate engages a distinct triple ionic interaction with the basic groove in the N-terminal region (K617, K655, and K805), which stands out when compared to the other phospho-sites (S908, T911 and S914).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we demonstrate how the requirement for S903 phosphorylation is also linked to transport activation. Nonetheless, CFTR studies have shown that combined PKA and PKC stimulation can drastically increase R-domain complex formation and activation (23, 46, 47). The phosphorylated S903 site phosphate engages a distinct triple ionic interaction with the basic groove in the N-terminal region (K617, K655, and K805), which stands out when compared to the other phospho-sites (S908, T911 and S914).…”
Section: Discussionmentioning
confidence: 99%
“…In purified samples, mutagenesis on CFTR and Ycf1 can diminish ATPase activity and can impact cellular activity (20, 21). Indeed, R-domain phospho-regulation seems to involve a complex kinase recruitment mechanism in which a myriad of phospho-sites that suggest PKA, PKC, CKII kinases can potentiate or suppress each other in the context of ABCC R-domain phosphorylation (22, 23). Recent work points to a specific PKA site (24), S813, as the predominant rate-limiting site, similar to the Ycf1 site S908 (20, 25).…”
Section: Introductionmentioning
confidence: 99%
“…1). Each MSD is composed of six transmembrane helices, of whichTM1-6 constitute MSD-1 and TM7-12 constitute MSd-2, followed by a cytoplasmic NBD (13). The MSD-2 and NBD-1 modules are connected by the r domain, a regulatory region with disordered structure that is unique to the CFTR gene and not found in other transporters (14).…”
Section: Mutations Of the Cystic Fibrosis Transmembrane Conductance Rmentioning
confidence: 99%
“…In [12][13][14][15][16][17][18] week-old abortive fetuses with CFTR gene mutations, the vas deferens is obstructed and denatured by mucus, and the vas deferens may be further aggravated in embryonic development (26). Furthermore, Gaillard et al (26) demonstrated that the expression of the CFTR in epididymal epithelium in human fetuses carrying CFTR mutations at 10-33 weeks of gestation was low, resulting in the production of highly viscous mucus by epithelial cells of the male genital tract.…”
Section: The Cftr Gene and Development Of The Vas Deferensmentioning
confidence: 99%
“…CBAVD as a genital type of cystic fibrosis is responsible for 2-6% of male infertility (Radpour et al, 2008). The clinical signs and symptoms of CBAVD, include slightly smaller or normal testicle size, atrophy in these testicles, or even lack of either the seminal vesicle or cauda epididymis or both.…”
Section: Introductionmentioning
confidence: 99%